Forgive and Forget?: Examining the Influence of Blame and Intentionality on Forgiveness Following Hypothetical Same-Sex Infidelity in the Context of Heterosexual Romantic Relationships. Issue 4 (3rd May 2020) - Denes, Amanda; Dillow, Megan R.; DelGreco, Maria; Lannutti, Pamela J.; Bevan, Jennifer L.
Abstract : The present study investigated responses to imagined same-sex infidelity committed by a partner in a heterosexual relationship. The motivational theory of infidelity and research on communicative infidelity were used as guiding frameworks for exploring differences in perceptions of blame and intentionality as a result of varying motivations for engaging in same-sex infidelity (i.e., cheating due to attraction, experimentation, sexual preoccupation, sexual depression, sociosexuality, jealousy, vengefulness, or not viewing the infidelity as cheating). It was predicted that greater perceptions of blame and intent would be associated with more negative transgression-related interpersonal motivations (i.e., more revenge and avoidance; less benevolence) and an increased expectation of terminating the relationship due to the partner's same-sex infidelity. Whether these relationships would replicate or differ according to the partner's motive for committing the hypothetical same-sex infidelity was also tested. Results revealed that, in general and across motives, attributions of blame were positively associated with revenge, avoidance, and relationship termination; perceived intentionality was positively associated with avoidance; and blame was negatively associated with benevolence. Furthermore, across most motives, blame was indirectly associated with relationship termination through avoidance and benevolence, and these associations were not moderated by biological sex. These findings and their implications for research on infidelity specifically, and relational functioning more broadly, are discussed.